2022
DOI: 10.3390/atmos13060957
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Year Climatology of the Wind Field Structure at Cape Baranova (Severnaya Zemlya, Siberia) from SODAR Observations and High-Resolution Regional Climate Model Simulations during YOPP

Abstract: Measurements of the atmospheric boundary layer (ABL) structure were performed for three years (October 2017–August 2020) at the Russian observatory “Ice Base Cape Baranova” (79.280° N, 101.620° E) using SODAR (Sound Detection And Ranging). These measurements were part of the YOPP (Year of Polar Prediction) project “Boundary layer measurements in the high Arctic” (CATS_BL) within the scope of a joint German–Russian project. In addition to SODAR-derived vertical profiles of wind speed and direction, a suite of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For the surface condition classification we use the land-sea and sea-ice masks of the respective RCMs. It should be noted that this empirical extrapolation does not account for effects of atmospheric stability or local topography, such as low-level jets, which may play also a role for WPD, since the wind maximum is typically at 100-300m height (Tuononen et al, 2015;Heinemann et al, 2022).…”
Section: Wind Power Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…For the surface condition classification we use the land-sea and sea-ice masks of the respective RCMs. It should be noted that this empirical extrapolation does not account for effects of atmospheric stability or local topography, such as low-level jets, which may play also a role for WPD, since the wind maximum is typically at 100-300m height (Tuononen et al, 2015;Heinemann et al, 2022).…”
Section: Wind Power Densitymentioning
confidence: 99%
“…Investigating the spatial and temporal variability of near-surface wind speed is critical to assess the current wind energy potential and evaluate its future changes as the world continues to warm (Pryor et al, 2005;Moemken et al, 2018). The local near-surface wind speed variability is determined by large-scale, synoptic, and meso-scale circulations (storms, polar lows) as well as local conditions (Jakobson et al, 2019;Fabiano et al, 2021;Heinemann et al, 2022;Rapella et al, 2023). Large-scale atmospheric circulation patterns such as NAO/AO affect the cyclone activity in the Arctic (Akperov et al, 2019) and impact on local wind characteristics (Laurila et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the representations of the wind, temperature, and moisture structure by the simulations were very good for the ABL and the troposphere. A comparison of wind profiles from SODAR measurements and RCM simulations for a three-year period in the area of Severnaya Zemlya (Siberia) showed a positive bias for a wind speed of about 1 m/s below 100 m, which increased to 1.5 m/s for higher levels [11].…”
Section: Introductionmentioning
confidence: 99%